T cells, more than antibodies, may prevent symptoms developing from respiratory syncytial virus infections in older adults - Salaun, Bruno; De Smedt, Jonathan; Vernhes, Charlotte; Moureau, Annick; Öner, Deniz; Bastian, Arangassery Rosemary; Janssens, Michel; Balla-Jhagjhoorsingh, Sunita; Aerssens, Jeroen; Lambert, Christophe; Coenen, Samuel; Butler, Christopher C.; et al. (Frontiers in Immunology, 2023)
The immune mechanisms supporting partial protection from reinfection and disease by the respiratory syncytial virus (RSV) have not been fully characterized. In older adults, symptoms are typically mild but can be serious in patients with comorbidities when the infection extends to the lower respiratory tract.Methods: This study formed part of the RESCEU older-adults prospective-cohort study in Northern Europe (2017-2019; NCT03621930) in which a thousand participants were followed over an RSV season. Peripheral-blood samples (taken pre-season, post-season, during illness and convalescence) were analyzed from participants who (i) had a symptomatic acute respiratory tract infection by RSV (RSV-ARTI; N=35) or (ii) asymptomatic RSV infection (RSV-Asymptomatic; N=16). These analyses included evaluations of antibody (Fc-mediated-) functional features and cell-mediated immunity, in which univariate and machine-learning (ML) models were used to explore differences between groups.Results: Pre-RSV-season peripheral-blood biomarkers were predictive of symptomatic RSV infection. T-cell data were more predictive than functional antibody data (area under receiver operating characteristic curve [AUROC] for the models were 99% and 76%, respectively). The pre-RSV season T-cell phenotypes which were selected by the ML modelling and which were more frequent in RSV-Asymptomatic group than in the RSV-ARTI group, coincided with prominent phenotypes identified during convalescence from RSV-ARTI (e.g., IFN-γ+, TNF-α+ and CD40L+ for CD4+, and IFN-γ+ and 4-1BB+ for CD8+).The evaluation and statistical modelling of numerous immunological parameters over the RSV season suggests a primary role of cellular immunity in preventing symptomatic RSV infections in older adults.